Enhancing Senior High School Teachers' Readiness in English Language Learning Based on Sasirangan and Augmented Reality - Siti Kustini; Rizky Amelia; Novita Triana; Heldiansyah Heldiansyah; Putriana Salman; Widya Ais Sahla (Carmin: Journal of Community Service, 2026)
This community service training aimed to strengthen senior high school English teachers' competencies in South Kalimantan by integrating local Sasirangan culture, augmented reality (AR) technology, and critical thinking skills into innovative instruction. Teachers had been facing several persistent challenges: reliance on conventional teaching methods, students' low English literacy, underdeveloped critical thinking skills, minimal use of local culture as a learning resource, and limited adoption of educational technologies like AR. To address these issues, the team designed and delivered a training program centered on integrating Sasirangan, AR, and critical thinking into grade XII English instruction. The program engaged 15 participants: 6 core workshop attendees, 7 community service team members, and 2 teaching assistants. Implementation followed seven stages, namely situational analysis, problem identification, goal setting, solution planning, social approach, activity implementation, and evaluation. During implementation, the team administered a pre-test, presented instructional content, led discussions and Q&A sessions, guided participants in designing learning activities, demonstrated the SasiVision AR application, and conducted a post-test to measure outcomes. Results demonstrated clear gains across three key indicators. Teachers showed a 50% increase in understanding and readiness to use Sasirangan as a contextual learning resource, a 40.7% increase in applying Android-based AR technology in English lessons, and a 14.1% increase in their ability to design activities that foster students' critical thinking. These findings indicate that the training successfully equipped teachers to integrate Sasirangan fabric as a meaningful, contextual resource in English language teaching, supported by the SasiVision AR application, offering a promising model for culturally grounded, technology-enhanced language instruction.